Signs of the plastid: Enzymes involved in plastid-localized metabolic pathways in a eugregarine species. (August 2021) - Yazaki, Euki; Miyata, Ryosuke; Chikami, Yasuhiko; Harada, Ryo; Kawakubo, Takashi; Tanifuji, Goro; Nakayama, Takuro; Yahata, Kensuke; Hashimoto, Tetsuo; Inagaki, Yuji
Abstract: Apicomplexa mainly comprises parasitic species and some of them, which infect and cause severe diseases to humans and livestock, have been extensively studied due to the clinical and industrial importance. Besides, apicomplexans are a popular subject of the studies focusing on the evolution initiated by a secondary loss of photosynthesis. By interpreting the position in the tree of eukaryotes and lifestyles of the phylogenetic relatives parsimoniously, the extant apicomplexans are predicted to be the descendants of a parasite bearing a non-photosynthetic (cryptic) plastid. The plastid-bearing characteristic for the ancestral apicomplexan is further strengthened by non-photosynthetic plastids found in the extant apicomplexans. The research on apicomplexan members infecting invertebrates is much less advanced than that on the pathogens to humans and livestock. Gregarines are apicomplexans that infect diverse invertebrates and recent studies based on transcriptome data revealed the presence of cryptic plastids in a subset of the species investigated. In this study, we isolated gregarine-like organisms (GLOs) from three arthropod species and conducted transcriptome analyses on the isolated cells. A transcriptome-based, multi-gene phylogenetic analysis clearly indicated that all of the three GLOs are eugregarines. Significantly, the transcriptome data from the GLO in a centipede appeared to contain the transcripts encoding enzymes involved in the non-mevalonate pathway for isopentenyl diphosphate biosynthesis and C5 pathway for heme biosynthesis. The enzymes involved in the two plastid-localized metabolic pathways circumstantially but strongly suggest that the particular GLO possesses a cryptic plastid. The evolution of cryptic plastids in eugregarines is revised by incorporating the new data obtained from the three GLOs in this study.